A tradição dos mantras no contexto do yoga integral (purna yoga): um estudo entre Brasil e Índia - Miranda, Roberto SIlva (2015)
Our dissertation main objective is to provide a critical view about the practice of mantras in the context of Purna Yoga (or Full Yoga), launching under the Sciences of Religions an ethnographical look over one of the main spiritual heritage of India, which continue to be part important Sadhana of several lines and branches of Yoga, thus seeking to understand these sounds, effects and their meanings. To have a general understanding of the Mantras we will discuss in the first chapter some of these sacred phonemes that are considered important for the tradition of Yoga. The mantras selected were: The OM mantra, the Gayatri Mantra, Mantra Hare Krishna (The Vaishnava Maha-Mantra). These are considered universal mantras that are practiced in various traditions, including the specific tradition on which we had observed the Purna Yoga or Full Yoga of Sri Aurobindo. In the second chapter we deepen concepts of Full Yoga and present elements of field research, through our travel experience by the ashrams of India, which experienced important practices of Yoga mantras linked to this. In the third chapter we present the results of interviews with leading masters and teachers of Full Yoga in different parts of India as well as Brazilian masters and instructors. In addition we also present a description of all the spiritual atmosphere of the visited ashrans through a participatory research in which the researcher, maintaining an academic look, experience the field through its praxis. We strive through our field research to observe exactly how these mantras are being practiced today in the context of full Yoga.